2011
DOI: 10.5354/0719-0581.2011.17935
|View full text |Cite
|
Sign up to set email alerts
|

Parentalidad y salud mental adolescente: diferencias entre ciudades y tipo de dependencia escolar

Abstract: Resumen los estilos de crianza influyen en la salud mental adolescente. trabajos previos han corroborado el modelo explicativo de brian barber que relaciona variables parentales (control psicológico, control conductual, apoyo social) con otras de funcionamiento adolescente (depresión, comportamiento antisocial, iniciativa social). este estudio pretende comprobar el modelo en tres ciudades de Chile y tipos de escuelas. Resultados: el modelo responde en la muestra total, pero presenta diferencias por ciudad y de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Parental PC has shown detrimental effects on child development in multiple cultural settings (Pettit et al, 2001;Barber et al, 2005;Finkenauer et al, 2005;Koçak et al, 2017;Symeou and Georgiou, 2017;Scharf and Goldner, 2018) including collectivist societies which perceive parental control as an expression of love and care (Gargurevich and Soenens, 2016). In Chile, parental PC has been scarcely studied, but the existing research results are consistent with the notion that PC has a negative effect on adolescent wellbeing (Casassus Rodino et al, 2011;Pérez and Cumsille, 2012).…”
Section: Introductionmentioning
confidence: 87%
“…Parental PC has shown detrimental effects on child development in multiple cultural settings (Pettit et al, 2001;Barber et al, 2005;Finkenauer et al, 2005;Koçak et al, 2017;Symeou and Georgiou, 2017;Scharf and Goldner, 2018) including collectivist societies which perceive parental control as an expression of love and care (Gargurevich and Soenens, 2016). In Chile, parental PC has been scarcely studied, but the existing research results are consistent with the notion that PC has a negative effect on adolescent wellbeing (Casassus Rodino et al, 2011;Pérez and Cumsille, 2012).…”
Section: Introductionmentioning
confidence: 87%
“…In Chile, a study carried out with adolescents from different cities also showed differences in the styles of parental socialization according to the sex of the sons and daughters, observing that the daughters perceived the father as neglectful more than the sons, and in the case of the mother, the daughters also perceived them as more neglectful [12]. Other Chilean studies show significant negative relationships between parental social support and depressive symptoms [17] and observe that the most predominant parenting style was that of authoritarian, which was significantly and positively related to the quality of family life [18].…”
Section: Introductionmentioning
confidence: 95%
“…Studies on parenting socialization styles in Latin America are scarce [17,18]. so, it is necessary to delve deeper into them, due to the importance of parenting practices in people's development.…”
Section: Introductionmentioning
confidence: 99%